(untitled) (Research, Society and Development, 2022)
The National Institutes of Science and Technology related to nanotechnology have been contributing to the production of scientific and technological research that can help in the development of new products and processes. This research aims to carry out a bibliometric analysis of the scientific production of the National Institutes of Science and Technology (INCTs) related to nanotechnology. The methodology consists of a quantitative exploratory research, which carried out a bibliometric analysis with data from the publications of nanotechnology INCTs, being analyzed a sample of two institutes that highlighted the scientific productions on their websites. The results indicated that scientific production has been growing between 2009 and 2020, however, it was noted that this production dropped from 2019 onwards, highlighting the need to explore more research in these institutes. Also, a keyword map was carried out, through the 118 documents found on INCTs in the Scopus database, highlighting words such as patents, research and technological development. And in the case of INCTs focused on nanotechnology, it was noted that the scientific productions showed the application of research to the area of medicine, and in the map developed based on these analyzed INCTs, the word nanoparticles appeared with greater evidence. Thus, it is understood that it is necessary to analyze the research that is being developed on nanotechnology, so that other studies can be explored on this topic, thus favoring the emergence of new products and processes.